Potential role of linagliptin as an oral once-daily treatment for patients with type 2 diabetes - Hoimark L (Dove Medical Press, 2012)
Lene Hoimark, Torben Laursen, Jørgen RungbyDepartment of Biomedicine – Pharmacology and Clinical Pharmacology, Aarhus University Hospital and Aarhus University, Aarhus, DenmarkBackground: Linagliptin is an oral antihyperglycemic agent that selectively inhibits the enzyme dipeptidyl peptidase-4 (DPP-4). Inhibition of DPP-4 increases the levels of the incretin hormones glucagon-like peptide and glucose-dependent insulinotropic polypeptide by preventing their degradation.Objective: We reviewed the role of linagliptin as an oral once-daily treatment for patients with type 2 diabetes.Methods: A comprehensive literature search was performed using the term “linagliptin.” Original research articles and review articles were included in our examination.Results: Linagliptin has a similar mode of action as other gliptins, with comparable efficacy, safety profile, and tolerability. Differences in pharmacokinetic parameters that distinguish linagliptin from other gliptins include that linagliptin is not renally excreted and does not require dose reduction with renal impairment.Conclusion: Linagliptin is an oral, once-daily, antihyperglycemic agent that significantly reduces glycated hemoglobin (HbA1c) when used alone or in combination with other antidiabetic drugs in people with type 2 diabetes. Pharmacokinetics, such as the lack of renal excretion, distinguishes linagliptin from other gliptins.Keywords: DPP-4 inhibitors, linagliptin, type 2 diabetes